Comparing Part-Solid and Pure-Solid Tumors in the TNM Classification of Lung Cancer (Eighth Edition) - Yamanashi, Keiji; Okumura, Norihito; Yamamoto, Yoshiharu; Takahashi, Ayuko; Nakashima, Takashi; Matsuoka, Tomoaki (The Thoracic and Cardiovascular Surgeon, 2019)
Background In the eighth edition of the TNM classification, the lung tumors that have the same solid components are categorized either as part-solid or pure-solid tumors. However, this is debatable since the tumors in the same T component categories were evaluated without considering this categorization, and was based on a more malignant behavior and a poorer prognosis of pure-solid tumors. The aim of this study was to investigate and compare the prognosis between part-solid and pure-solid tumors.Methods We retrospectively analyzed 530 patients who were diagnosed with clinical-T1a-cN0M0 non–small-cell lung cancer (NSCLC) and were treated surgically. The subjects were divided into part-solid and pure-solid tumor groups using thin-section computed tomography. The prognosis was compared between the groups.Results Although relapse-free survival (RFS) was significantly shorter in the pure-solid tumor group (p = 0.016), no significant differences were observed in the overall survival (OS) between the two groups (p = 0.247). In 137 propensity score–matched pairs, including variables such as age, gender, Brinkman index, body mass index, forced expiratory volume in 1 second/forced vital capacity, Charlson comorbidity index, carcinoembryonic antigen levels, clinical-T status, surgical procedure, and extent of surgery, no significant differences were seen in the RFS and OS between the two groups (p = 0.709 and p = 0.517, respectively).Conclusion In the eighth edition of the TNM classification of clinical-T1a-cN0M0 NSCLC, the prognosis of part-solid and pure-solid tumors showed no significant differences. Solid component size of the tumor is considered important prognostic factor in early-stage NSCLC.
Keywords: surgery; lung cancer treatment; lung cancer; diagnosis; VATS